Morphological and genetic variability of chili pepper (Capsicum annuum L.) populations from northern of Mexico - Ibarra-Legarda, Karina; Infante-Ramirez, Rocío; Robles-Hernández, Loreto; Gonzalez-Franco, Ana; Muñoz-Ramirez, Zilia; Delgado-Gardea, Ma. Carmen (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
This study investigated the genetic and morphological variability of five domesticated chili varieties (Árbol, Güerito, Mirasol, Negro and Alcalá) and one wild variety (chiltepín) from Chihuahua, Mexico. Morphological evaluation was carried out according to the International Plant Genetic Resources Institute, combining correspondence analyses and Chi-square tests. Genetic variability was determined using the RAPD technique; a dendrogram was constructed, and genetic diversity among populations was estimated using principal coordinate methods, Shannon index, and permutational multivariate analysis. The morphological analysis revealed significant variations, while the genetic analysis, using the RAPD technique, showed 79.5 % polymorphism, indicating considerable diversity among the varieties. The dendrogram revealed the presence of three groups, highlighting chiltepín as potential ancestor of the domesticated varieties. The study emphasizes the importance of conserving and improving these plant genetic resources.